Chronic gastritis and gastroduodenal ulcer: a case control study on risk of coexisting duodenal or gastric ulcer in patients with gastritis. Issue 7 (July 1989) - Sipponen, P; Seppälä, K; Aärynen, M; Helske, T; Kettunen, P
Abstract : Chronic (atrophic) gastritis (AG) is common in active duodenal (DU) and gastric ulcer (GU) disease. In this case control study in consecutive prospective outpatients (571 cases and 1074 controls) who had undergone diagnostic upper gastrointestinal endoscopy and routine biopsies from both antral and body mucosa, we calculated the risk of coexisting active DU and/or GU in different gastritis of the antrum or body and according to grade (superficial gastritis, mild, moderate or severe atrophic gastritis). The risk of coexisting active gastroduodenal ulcer (ulcer in duodenum and/or stomach), as well as the risk of DU or GU, was dependent upon the presence and grade of gastritis in antrum and body mucosa. The risk of coexisting ulcer, as expressed as an age adjusted relative risk (RR) and calculated as odds ratio of gastritis in cases and controls, was significantly increased in the presence of superficial antral and body gastritis (RR = 8.5 (7.0-20.0) in men; RR = 5.8 (3.3-10.2) in women), as compared with the risk of ulcer in subjects with histologically normal mucosa (RR = 1). The risk of ulcer, and the risk of GU in particular, increased further with increasing severity of antral gastritis. In such patients with moderate or severe atrophic antral gastritis the RR of coexisting ulcer even exceeded 20 in men and 10 in women (RR = 25.6 (9.0-72.7) in men; RR = 11.7 (5.9-23.0) in women). On the other hand, the RR of ulcer, and the RR of DU in particular, was below 1 in the presence of atrophic gastritis in the gastric body, irrespective of the grade of gastritis in the antrum. We conclude that the type and grade of gastritis strongly predicts the risk of coexisting peptic ulcer, and that the risk of coexisting DU or GU increases with an increase in grade of AG of the antrum but decreases with an increase in grade of AG of the gastric body.